Eternal: Interpretasi Puisi Simbol “Q” Karya Sutardji Calzoum Bachri - Abizar Algifari Saiful; Pande Made Sukerta (Jurnal Kajian Seni, 2021)
ABSTRACTThe work "Eternal" is a musical composition performance that adopts the meaning and significance of Sutardji Calzoum Bachri's symbolic poem "Q" as the base idea. The results of an in-depth observation of Sutardji Calzoum Bachri's symbolic poem "Q" are five main points which are derived from the interpretation of the author.  The five points are (1) We (humans) and God have different positions, different substances and different characteristics, unimaginably different, so humans need guidance ('Q' = al-Quran) in order to reach Him;  (2) Humans will always be limited in any ways as 'humans’, in contrast to creators and beings who are assigned the title alif, lam, mim;  (3) As human beings who have reason and sense, we’ll always look for meanings and be side by side with the universe (habluminallah and habluminannas);  (4) Confusion makes people speculate on everything;  and (5) In the end, questions will end in questions again. These points are used as the basis for the theme or the atmospheric description for creating the materials for the musical and working on each of the musical compositions in "Eternal".  The musical compositions are as follows: "Aku", "Q", "Seru!", "Alif Lam Mim", and "Tanya". The composition of the musical "Eternal" goes through three stages, namely the preparation of content ideas, the preparation of the composition ideas, and the actual composing.                        Keywords: Eternal, Music Analyzer, The Symbolic Poem “Q” ABSTRAKKarya “Eternal” adalah pertunjukan komposisi musik yang mengangkat arti dan makna puisi simbol “Q” karya Sutardji Calzoum Bachri sebagai ide gagasannya. Hasil pengamatan mendalam terhadap puisi simbol “Q” karya Sutardji Calzoum Bachri dapat ditemukan lima poin utama yang berasal dari hasil interpretasi pengkarya. Kelima poin tersebut yaitu (1) Kita (manusia) dan Tuhan memiliki perbedaan posisi, perbedaan zat dan perbedaan sifat, jauh tak terbayangkan, maka manusia butuh pedoman (‘Q’=al Quran) untuk sampai pada-Nya; (2) Manusia akan selalu terbatas dalam kadarnya sebagai ‘manusia’, berbeda dengan pencipta dan makhluk yang diberi predikat alif, lam, mim; (3) Sebagai manusia yang memiliki akal senantiasa mentadaburi (mencari makna) dan bersanding dengan alam semesta (habluminallah dan habluminannas); (4) Kebingungan membuat manusia berspekulasi terhadap segala hal; dan (5) Pada akhirnya pertanyaan akan berakhir pada pertanyaan kembali. Poin-poin tersebut digunakan sebagai titik pijak tema atau penggambaran suasana untuk menyusun materi musikal dan garap masing-masing komposisi musik dalam karya “Eternal”. Adapun komposisi musik tersebut sebagai berikut. “Aku”, “Q”, “Seru!”, “Alif Lam Mim”, dan “Tanya”. Penyusunan karya musik “Eternal” menggunakan tiga tahapan, yaitu penyusunan gagasan isi, penyusunan ide garapan, dan penuangan ide garapan. Kata kunci: Eternal, Analisa Musik, Puisi Simbol “Q”